(3ZGjI GdEJbGf aj JOHjQ HOf GdEfSGfs - (3UGdM Hf fUQ Hf Sdhe GdMdHj,J (B1081 (3g` s
(3ChdgG (B:s
(3hHYO adeG cGf Yde GdWH HMQkG dGjOQc dg bQGQ, hJjgkG hGSYkG dGjTb dg ZHGQ hbO nOhf aj CUhdg haQhYg GdCSGWjQ ef MceGA GdjhfGf hGWHGA GddGJjf eGdG jYO hdGojMUi ef GdCSaGQ s
(3BNQgG (B:s
(3hSaha CQeGJjce GdQhRG, Ke ef cd hGMO fUa OQge SfHd , hEP NQ eci ef hGMO SJI GhQGb s
(3fSNI NGeSIs
(3HChdgG agQS HCfhGY GdCeQGVs
(3hHBNQgG Jedjc eDQN HSfI (B1235 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B165 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdWHs